Molecular Cloning, Characterization, and Expression of MiSOC1: A Homolog of the Flowering Gene SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 from Mango (Mangifera indica L) - Wei, Junya; Liu, Debing; Liu, Guoyin; Tang, Jie; Chen, Yeyuan (Frontiers in Plant Science, 2016)
MADS-box transcription factor plays a crucial role in plant development, especially controlling the formation and development of floral organs. Mango (Mangifera indica L) is an economically important fruit crop, but its molecular control of flowering is largely unknown. To better understand the molecular basis of flowering regulation in mango, we isolated and characterized the MiSOC1, a putative mango orthologs for the Arabidopsis SUPPRESSOR OF OVEREXPRESSION OF CO1/AGAMOUS-LIKE 20 (SOC1/AGL20) with homology-based cloning and RACE. The full-length cDNA (GenBank accession No.: KP404094) is 945 bp in length including a 74 bp long 5’ UTR and a 189 bp long 3’ UTR and the open reading frame (ORF) was 733 bps, encoding 223 amino acids with molecular weight 25.6 kD. Both sequence alignment and phylogenetic analysis all indicated that deduced protein contained a conservative MADS-box and semi-conservative K domain and belonged to the SOC1/TM3 subfamily of the MADS-box family. Quantitative real-time PCR (qRT-PCR) was performed to investigate the expression profiles of MiSOC1 gene in different tissues/organs including root, stem, leaves, flower bud and flower. The result indicated MiSOC1 was widely expressed at different levels in both vegetative and reproductive tissues/organs with the highest expression level in the stems，leaves and inflorescences, low expression in roots and flowers. The expression of MiSOC1 in different flower developmental stages was different while same tissue –specific pattern among different varieties. In addition, MiSOC1 gene expression was affect by ethephon while high concentration ethephon inhibit the expression of MiSOC1. Overexpression of MiSOC1 resulted in early flowering in Arabidopsis. In conclusion, these results suggest that MiSOC1 may act as induce flower function in mango.